Comparative Genomic Analysis Reveals Genetic Mechanisms of the Variety of Pathogenicity, Antibiotic Resistance, and Environmental Adaptation of Providencia Genus - Yuan, Chao; Wei, Yi; Zhang, Si; Cheng, Juan; Cheng, Xiaolei; Qian, Chengqian; Wang, Yuhui; Zhang, Yang; Yin, Zhiqiu; Chen, Hong (Frontiers in Microbiology, 2020)
The bacterial genus Providencia is Gram-negative opportunistic pathogens, which have been isolated from a variety of environments and organisms, ranging from humans to animals. Providencia alcalifaciens, Providencia rettgeri, and Providencia stuartii are the most common clinical isolates, however, these three species differ in their pathogenicity, antibiotic resistance and environmental adaptation. Genomes of 91 isolates of the genus Providencia were investigated to clarify their genetic diversity, focusing on virulence factors, antibiotic resistance genes, and environmental adaptation genes. Our study revealed an open pan-genome for the genus Providencia containing 14720 gene families. Species of the genus Providencia exhibited different functional constraints, with the core genes, accessory genes, and unique genes. A maximum-likelihood phylogeny reconstructed with concatenated single-copy core genes classified all Providencia isolates into 11 distant groups. Comprehensive and systematic comparative genomic analyses revealed that specific distributions of virulence genes, which were highly homologous to virulence genes of the genus Proteus, contributed to diversity in pathogenicity of Providencia alcalifaciens, Providencia rettgeri, and Providencia stuartii. Furthermore, multidrug resistance (MDR) phenotypes of isolates of Providencia rettgeri and Providencia stuartii were predominantly due to resistance genes from class 1 and 2 integrons. In addition, Providencia rettgeri and Providencia stuartii harbored more genes related to material transport and energy metabolism, which conferred a stronger ability to adapt to diverse environments. Overall, our study provided valuable insights into the genetic diversity and functional features of the genus Providencia, and revealed genetic mechanisms underlying diversity in pathogenicity, antibiotic resistance and environmental adaptation of members of this genus.